Passion, Purpose, Profit 9 Keys to Building an Authentic Executive Coaching Business. - Karaba, Donna (Morgan James Publishing, 2019)
A guide for leaders who want to follow their calling'without missing their kids' soccer games: "Will inspire you to live an integrated, joy-filled life."'Marshall Goldsmith, New York Times-bestselling author of What Got You Here Won't Get You There Leaders can see the knowledge, curiosity, and imagination that goes into successfully coaching executives. They can navigate the executive boardroom and coach with confidence. But how does a leader inspire joy while also being fully present in their children's lives' How does a leader'and a mom'build confidence in her clients and family' In Passion Purpose Profit, Donna Karaba gives leaders the keys to transforming lives and helping others fulfill their potential by modeling an integrated life. She uses her time-tested business blueprint, The Authentic Leadership Business Model, to teach the principles that allow leaders to grow relationships in the workplace and in the home. Leaders discover how to coach executives to self-actualization, manage client relationships, and create real value, among other things. Passion Purpose Profit is the roadmap for anyone who wants to bring in a high net income without sacrificing their family.